Will 'structural reforms' of labour markets reduce productivity growth? A firm-level investigation - Robert Vergeer; Steven Dhondt; Alfred Kleinknecht; Karolus Kraan (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
More 'flexible' labour relations significantly reduce labour productivity growth in sectors that tend towards a 'routinised' (other than a 'garage business') innovation regime. We argue that structural reforms that make firing easier will diminish the loyalty and commitment of workers, making accumulation of (tacit) knowledge more difficult. It also reduces training, increases knowledge-leaking to competitors and favours autocratic management and the growth of management and control bureaucracies. Our results are consistent with findings in macro-level studies that wage-cost saving flexibilisation of labour relations and downward wage flexibility reduce labour productivity growth: a 1 per cent wage change causes a ≈ 0.4 per cent change in value added per labour hour.
Keywords: J5; O3; 330; flexible labour; labour productivity; innovation regimes; varieties of capitalism